L.P. Karsavin’s dialogue metaphysics - Суходуб, Т. Д. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2019)
In the introduction, the topicality of formation of dialogue culture in contemporary society is substantiated. Dialogue is regarded as a way of overcoming aggressive-conflictual forms of «social communication» (L. Karsavin’s term). The aim of the research is to present L. Karsavin’s metaphysics as a philosophy of dialogue. The research tasks are to point out both peculiarities of L. Karsavin’s philosophical thinking and the ways he interprets the problem of dialogue. There were employed the following research methods: biographical, hermeneutical, cultural-semantic analysis. Research result was a conceptual assessment of L. Karsavin’s philosophical study as a «philosophy of dialogue». Traditionally, the thinker’s body of work is referred to as either «metaphysics of unitotality» or Christian-Orthodox rationalism (according to P. Gaidenko, V. Zenkovsky, N. Motroshilova, S. Khoruzhiy, B. Yakovenko and others). Nevertheless, the article argues that it makes sense to determine L. Karsavin’s philosophical path as a search for opportunities and conditions for evolving the culture of dialogue. The metaphysics of the Other is represented by Karsavin: as a link between personality and the «Other» (Absolute); as a cosmic mission of a human being; as a human destiny as it is («intermutual unity with the beloved»); as a communicative nature of «social personalities» that determine each other’s lives. Within the framework of the research discussion, the works of the following scientists were particularly interesting: E. Kovaleva, Yu. Melikh, O. Nazarova, S. Khoruzhiy and others, who draw attention to the issues like those: the role of consistency in the development of cultural traditions; the link between the philosopher’s personalism and European philosophy; understanding intercultural philosophical communication as a dialogue of cultures; introducing the concept of «ontological drama», which underlies an appropriate interpretation of Karsavin’s study etc. Author’s reflections on the problem posed in the article were constructed according to «complementarity principle». Conclusions: the dialogue is presented in L. Karsavin’s works as a fundamental principle of philosophizing, a metaphysical problem, a philosophical genre. The following categories of Karsavin’s discourse – multi-unity, symphonic personalities, culture as a symphonic personality, the world of the other people, etc. – enables us to reveal the meaning of the dialogue as a way of overcoming the antagonisms of the being.